PEMBENTUKAN DAN PENGAWASAN PRODUK HUKUM DAERAH - Sukriono, Didik (JURNAL KONSTITUSI, 2011)
Area autonomy is often translated by local government of identical at the increasing of native earnings of region (PAD) as much as possible. By law (Perda) represent looked into instrument